Nonsteroid anti-inflammatory drug choices in patients with juvenile idiopathic arthritis: A systematic review - Yogi Priyatna Biantara; Surya Fajari Widhiarma; Widia Trilaksana Kusuma (DiscoverSys Inc., 2022)
Background: Disease-modifying anti-rheumatic drugs (DMARDs) are still a priority in treating juvenile idiopathic arthritis (JIA). The choice of drug therapy for the NSAIDs as an alternative to the therapy used in managing JIA cases due to the side effects of DMARDs. However, the former discussion of the choices therapy of NSAID therapy in JIA patients is still limited. This systematic review was conducted to present any choices of NSAIDs used for the treatment JIA and presented their effectiveness and adverse reaction compared with other NSAIDs used for treating JIA. Methods: Comprehensive electronic searches were performed in PubMed/Medline, EMBASE, and Cochrane Library, choosing Randomized Controlled Trials of NSAIDs for treating children with JIA up to January 2009. The risk of bias was assessed using the Cochrane Risk of Bias Tools for randomized controlled trials. Results: Eight eligible randomized controlled trials (RCT) out of 1309 studies were included, with a total of 1112 participants with JIA identified, addressing 19 kinds of interventions with nine types of medications. First RCT concluded that Celecoxib 3 mg/kg and Celecoxib 6 mg/kg were at least as effective as naproxen 7.5 mg/kg in terms of reducing clinical symptoms of arthritis and joint swelling. Second RCT concluded that Low Dose (0,3 mg/kg) and High Dose (0.6mg/kg) Rofecoxib showed a greater improvement than the Naproxen group to relieve the pain. The third RCT stated that good efficacy or satisfaction is most frequent in the participant with Meloxicam 0.125 mg/kg rather than Meloxicam 0.25 mg/kg or Naproxen 10 mg/kg. Fourth RCT concluded that Ibuprofen 30-40 mg/kg/d is an effective agent for symptomatic treatment of JIA and is well-tolerated in many children. Fifth RCT informed that Piroxicam show more effective in controlling the symptoms and improving function than Naproxen 10 mg/kg/day. Sixth RCT concluded that Acetylsalicylic acid 75 mg/kg/day has better efficacy than Naproxen 10 mg/kg/d in relieving the symptoms. The seventh study stated that both diclofenac sodium 2-3 mg/kg/day and acetylsalicylic acid 50-100 mg/kg/d at least as good as placebo. The last RCTs study stated that tolmetin 15 mg/kg/day decreased the duration of morning stiffness and reduced joint pain. Also, aspirin 50mg/kg/day resulted in ROM improvement in JIA patients. Conclusions: We present Celecoxib, Rofecoxib, Meloxicam, Ibuprofen, Piroxicam, Acetylsalicylic Acid (ASA), Diclofenac Sodium, Tolmetin Sodium, and Naproxen as the NSAIDs choice drugs on pediatric patient diagnosed with JIA. which has each adverse event on each therapy.